Improving Student Activities and Learning Outcomes through the Application of the Virtual Field Trips Learning Model - Moh. Imron Rosidi; Ismaul Fitroh (Jurnal Ragam Pengabdian, 2025)
History learning in the Indonesian History during the Hindu-Buddhist Period course has not yet implemented innovative learning models and has limited historical learning resources. This has resulted in students not being interested in learning. The purpose of this study was to improve students' history learning outcomes by implementing a virtual field trip learning model. This study used classroom action research conducted in two cycles. The results of this study can be seen from the percentage of student activity and learning outcomes. Student learning activity in cycle I reached 71.17%, and in cycle II, the percentage of student learning activity reached 85.98%. In cycle I, 25 out of 37 students completed the course, or 67.57%, with a moderate category. Meanwhile, in cycle II, 31 out of 37 students completed the course, representing 83.78% with a very good category. Based on this data, the success indicators in this study have been achieved, so it can be concluded that the use of the virtual field trips learning model can improve student activity and learning outcomes.